Pengembangan Media Pembelajaran Puemla pada Materi Pengamalan Sila Pancasila di Kelas 2 SDN Klagen - Amaris Evania Putri; Risda Lailul Yulfa Fitria; Eli Masnawati; Masfufah Masfufah ; Febriarsita Eka Sasmita; Rahayu Mardikaningsih; She Fira Azka Arifin; Didit Darmawan (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2023)
The development of puemla learning media on the material of practicing the Pancasila precepts of Pancasila learning subjects in grade 2 elementary schools is intended to facilitate understanding of the material, obtain meaningful learning and increase motivation in learning. Learning media is a learning tool that helps students improve their thinking, attention, and abilities or skills. the method used is 4D which consists of define, design, develop, and dessiminate. (1) the defining stage of define is to conduct a needs analysis on students, which aims to find out the basic problems needed in the development of learning media and to find out about the advantages and disadvantages of learning media used by teachers so far, media analysis, and analysis of students, (2) the design stage of design that is done first is to choose material that suits the characteristics of students, (3) the development stage of develop is the process of creating it into reality, (4) the spread of dessiminate is a real rarity whether the learning system that is built is successful, in accordance with expectations or not. The results showed that puemla learning media can increase the motivation of students and in accordance with the characteristics of students who can be used as a means of supporting the learning process as evidenced by the evaluation of the board of teachers at SDN Klagen, Wilayut village, Sukodono District and the enthusiasm of students in grade 2.